Digital informed consent: Possibilities and challenges in biobanks for health research - Riso, B.; Águas, C. (Cadernos de Saúde Societal, 2022)
Biobanks are key infrastructures in biomedical research, storing and providing biological samples, personal and clinical data. Informed con- sent is a central piece of the process, as a means to respect each parti- cipants’ dignity, integrity and to acknowledge their capacity to express autonomous decisions. Providing adequate information, while ensuring the voluntariness of their decision are essential to an effective consent. Requesting informed consent usually takes place in the context of heal- thcare, where paper forms are still widely preferred, when not manda- tory and when person to person relationships are crucial. As biobanks are moving fast to implement automated protocols from biological samples processing to data collection, it is relevant to discuss the challenges posed by the digitalization of informed consent. To this end, such transition will be critically discussed using dynamic consent as a starting point to highlight the opportunities of digital tools, but also the relevance of healthcare context.